Agricultural carbon emissions in China: measurement, spatiotemporal evolution, and influencing factors analysis - Huang, Xiujing; Wu, Xinyu; Guo, Xiaoyang; Shen, Yang (Frontiers in Environmental Science, 2024)
This paper aims to explore the spatiotemporal evolution characteristics and influencing factors of China's agricultural carbon emissions from 2000 to 2022. Agricultural carbon emissions were calculated using the emission factor method, based on data obtained from the China Rural Statistical Yearbook and the statistical yearbooks of various provinces, revealing a fluctuating upward trend in total emissions. Through the application of the standard deviation ellipse analysis method and the center of gravity migration model, the spatial distribution migration path of agricultural carbon emissions in China was uncovered, indicating a gradual shift of the center towards the central and western regions, reflecting changes in agricultural production activity areas. Regional disparities and driving factors of agricultural carbon emissions were further analyzed using the Theil index and the Logarithmic Mean Divisia Index (LMDI) model. The results indicate that intraregional differences are the primary factors contributing to the imbalance in agricultural carbon emissions, with the disparity being particularly pronounced in grain production and consumption balance regions. Additionally, factors such as agricultural production efficiency, adjustments in the agricultural industrial structure, economic structure and output, and urbanization levels were found to significantly influence carbon emissions. Among these, the economic output effect and urbanization effect are identified as the primary drivers of increased carbon emissions, while declining production efficiency has inhibited emission reduction efforts.